Waking Dragons - Yolen, Jane; Anderson, Derek 1969- (New York : Simon & Schuster Books for Young Readers, 2012)
In the morning, dragons wake up, tumble out of bed, and get ready to fly into the sky.
Keywords: Dragons -- Fiction; Stories in rhyme